Leaving Mother Lake : a girlhood at the edge of the world - Namu, Yang Erche 1966-; Mathieu, Christine (Boston : Little, Brown, 2002)
A young Chinese woman describes growing up in Moso country in the Himalayas, among her people's unique matrilineal society, and the conflicts with her strong-willed mother that led her to leave her mother's home to create a life of her own
Accelerated Reader AR
Keywords: Yang Erche Namu, -- 1966-; Women singers -- China -- Biography